SMART IRRIGATION SYSTEM - Prof. Shaikh Z. A. R.; Mr. Alankar Suryawanshi; Mr. Ram Suryawanshi; Mr. Bhanudas Suryawanshi; Mr. Dinesh Rampure (International Journal of Innovations in Engineering Research and Technology, 2023)
In daily operations related to farming or gardening watering is the most important practice and the most labor-intensive task. No matter what whichever weather is, either too hot and dry or too cloudy and wet, you want to be able to control the amount of water that reaches your plants. Modern watering systems could be effectively used to water plants when they need them.